Influence of concrete and unbonded ratio on RC beams - Yang, Jianhui; Wang, Li; Yang, Dongbo; Wang, Qinting (Construction & building materials, 2023)
•The unbonded ratio is the main factor affecting the performance of an RC beam.•The friction coefficient between the rebar and concrete is related to the load stage. Hybrid aggregates, comprising normal-weight and lightweight aggregates, offer an effective means to enhance the physical and mechanical properties of concrete. However, the comprehensive effect of hybrid aggregate concrete on the flexural performance of reinforced concrete (RC) beams remains largely unexplored. In this study, utilizing LC30 lightweight concrete, LC40 gravel lightweight concrete, hybrid aggregate lightweight concrete, and hybrid aggregate concrete with reduced ceramsite content as matrix materials, RC ordinary beams and RC bond-slip beams with dimensions of 150 mm × 300 mm × 2400 mm were meticulously designed and fabricated. Employing a four-point bending test, the effects of the concrete matrix, the unbonded ratio, and the reinforcement ratio of the bottom longitudinal rebar on the flexural behavior of the two types of beams were scrutinized. Furthermore, the load–deflection and load–slip responses were subjected to numerical simulation using the finite element method. The findings demonstrate that hybrid aggregates exert a substantial influence on adjusting the dry apparent density, strength, and elastic modulus of concrete to align with design specifications. While the physical and mechanical characteristics of both beam types are primarily governed by the reinforcement ratio and unbonded ratio, the concrete matrix, despite its distinct properties, exhibits minimal effect on these attributes. Nevertheless, it significantly affects beam stiffness and the relative slip between the rebar and the concrete matrix. Both beam categories adhere to the plane section assumption and reveal that optimal collaborative performance between the rebar and concrete matrix occurs at a bottom longitudinal reinforcement ratio of 1%, albeit diminishing with escalating unbonded ratios. The failure progression of both beam types can be categorized into three stages: elastic phase, crack propagation phase, and compressive failure phase. The process of crack advancement, the load–deflection profile, and the load–slip behavior of the beams manifest similarities, albeit subject to variations attributable to the concrete matrix, bottom longitudinal reinforcement ratio, and unbonded ratio. The Menetrey–Willam constitutive model effectively replicates the load–deflection and load–slip characteristics of both beam types. However, its simulation precision is influenced by the friction coefficient existing between the rebar and the concrete matrix. Notably, this friction coefficient undergoes alteration in consonance with the concrete failure process, thereby reflecting the gradual degradation of bonding performance between the rebar and the concrete matrix.